Bilateral Ureteral Leiomyoma With Bilateral Ureteropelvic Junction Obstruction - Hsun-Shuan Wang; Chun-Hsiung Huang; Ming-Tan Chen; Wen-Jeng Wu (Kaohsiung Journal of Medical Sciences, 2010)
Leiomyomas are benign tumors characterized by overgrowth of visceral smooth muscle in the respiratory, gastrointestinal, and female reproductive tracts. They rarely develop in the urinary system and only 10 cases of unilateral ureteral leiomyoma (UL) have been reported since 1955. No cases of bilateral UL or ureteropelvic junction obstruction due to UL have ever been reported. We present a case of bilateral UL with bilateral ureteropelvic junction obstruction. To the best of our knowledge, this is the first such case report in the English literature.